Power losses reduction by optimal allocation of renewable distributed generation in distribution networks - Boukaroura, Abdelkader; Amroune, Mohammed (جامعة الوادي Université ofEl-Oued, 2023)
The electrical energy demand is increasing dramatically in many countries around the world due to population growth. As a result of this significant increase in demand, electricity distribution companies are seeking to promote distributed generation (DG). With the growing integration of decentralized renewable power generation into the distribution network, it becomes an active circuit where power flows and voltages are influenced not only by loads but also by sources. In distribution networks (DN), the optimal allocation of Renewable Distributed Generation (DG) units can significantly improve system performance by reducing power losses and enhancing the voltage profile and stability of the radial distribution network. The main objective of this paper is to apply the marine predator algorithm (MPA) to optimize the siting and sizing of DG units in the DN. The objective function considered is the minimization of active power losses. The proposed algorithm is tested on the IEEE 33-bus and 69-bus DN. The simulation results demonstrate that the MPA algorithm outperforms other optimization algorithms in terms of perform
Article
Keywords: Distribution network, Renewable distributed generation, Marine predator algorithm, Power losses.